Basal thumb osteoarthritis surgery improves health state utility irrespective of technique: a study of UK Hand Registry data - Lane, J; Rodrigues, JN; Furniss, D; Burn, E; Poulter, R; Gardiner, M (SAGE Publications, 2020)
We used UK Hand Registry data to study two aspects of basal thumb osteoarthritis surgery: first, whether health-related quality of life improves after surgery. Second, whether results from trials comparing simple trapeziectomy and trapeziectomy with ligament reconstruction and tendon interposition are reproducible in routine clinical practice. Prospectively collected EQ5D index and Patient Evaluation Measure part 2 data were compared at baseline and at 3, 6, and 12 months postoperatively in 1456 patients (median age 67 years; 78% female). A mixed-effects regression model was also used to determine the postoperative trajectory of these variables. There was a significant improvement in the EQ5D index (median + 0.15; (interquartile range 0 to 0.40)) and Patient Evaluation Measure (–22; (–33 to –10)) by 1 year postoperatively and with no meaningful difference between the two techniques. This study demonstrates health state utility gains after basal thumb osteoarthritis surgery regardless of surgical techniques used.